Committee 'C' on Draft Third Five Year Plan (Agriculture and Rural Economy) Synopsis of Proceedings (10th, 11th, and 12th November, 1960) - Planning Commission (Planning Commission, 1960)
The first sitting of Committee ‘C’ on the Draft Third Five Year Plan was held at 3 p.m. on Thursday, the 10th November, 1960 in the Central Hall, Parliament House, New Delhi. Dr. Ram Subhag Singh took the Chair. The Chairman welcomed the Members of the Committee and said that the idea of the Speaker of the Lok Sabha and the Chairman of the Rajya Sabha that the draft of the Third Five Year Plan should be discussed Programme by different committees of the Members of Parliament was good and that whatever suggestions were offered by them should be duly taken note of by the Planning Commission and the Government.
Synopsis of Proceedings (10th, 11th, and 12th November, 1960)
Planning Commission Library Government of India